Emerging health risks from agricultural intensification in Southeast Asia: a systematic review. (3rd July 2017) - Lam, Steven; Pham, Giang; Nguyen-Viet, Hung
Abstract: Background: Agricultural intensification is having profound impacts on food security and rural livelihoods; however, concerns remain about the potential implications on public health. Objectives: We aim to examine and synthesize the evidence for human health risks of agricultural intensification in Southeast Asia. Methods: We conducted a systematic review of peer-reviewed articles published between January 2000 and December 2015 from two electronic databases (PubMed, CAB Direct). Results: A total of 73 relevant studies were included and evaluated. More than half of the studies used epidemiological methods while others applied alternative methods to quantify or estimate risks. Studies mainly focused on occupational and consumer exposure to pesticides, without often specifying the actual health risk. Conclusion: Overall, the current knowledge on health risks appears to be limited. More research on long-term health implications and a wider range of contaminants are needed if sustainable benefits are to be obtained from agricultural intensification.